If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3w + 6 = w + 9 + -2w Reorder the terms: 6 + -3w = w + 9 + -2w Reorder the terms: 6 + -3w = 9 + w + -2w Combine like terms: w + -2w = -1w 6 + -3w = 9 + -1w Solving 6 + -3w = 9 + -1w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add 'w' to each side of the equation. 6 + -3w + w = 9 + -1w + w Combine like terms: -3w + w = -2w 6 + -2w = 9 + -1w + w Combine like terms: -1w + w = 0 6 + -2w = 9 + 0 6 + -2w = 9 Add '-6' to each side of the equation. 6 + -6 + -2w = 9 + -6 Combine like terms: 6 + -6 = 0 0 + -2w = 9 + -6 -2w = 9 + -6 Combine like terms: 9 + -6 = 3 -2w = 3 Divide each side by '-2'. w = -1.5 Simplifying w = -1.5
| 19x+5=15x+5 | | log(x)+log(x-1)=log(3x+12) | | Y=20-3(2.727272727273) | | 3.5j-17j-17.26=-9.5j+19.54 | | 6w+3=7w | | x(x-9)=70 | | 4x+2x(.5-5)=0 | | y=5(3a+4b) | | Y=2.5(2.727272727272727273)+5 | | ab+-6ab= | | 6i*8i= | | 4a+8s= | | .33x+1=-7 | | 12+3000=4200 | | 10x-163=3x-9 | | 2(-3)(5-10)+9= | | 3(c-bx)=18 | | an+-6ab= | | 3y+9=5y+5y | | 20.88h=145 | | 7-7=9 | | 2.7f+18.87=0.8f-16.66 | | M-6.25=44.25 | | 11x=10x+(-10) | | ln(x*2+5x+6)=ln(x+11) | | -3(5x+3)-(x-3)= | | 2.5x+5=20-3x | | 15c+7w=47 | | 18x^2+48x-96= | | Y=-14+6x | | 5n-3=29+n | | X-5.2=1.92 |